THE INFLUENCE OF ENVIRONMENTAL COSTS, ENVIRONMENTAL PERFORMANCE AND FIRM SIZE ON FINANCIAL PERFORMANCE WITH ENVIRONMENTAL DISCLOSURES AS AN INTERVENING VARIABLE - Siswanto; Nurna Aziza; Madani Hatta (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
This research is to prove and analyze the Effect of Environmental Costs, Environmental Performance, and Company Size on Financial Performance with Environmental Disclosure as an Intervening Variable. The samples are mining sector companies listed on the Indonesia Stock Exchange in 2019-2023. The direct test results produce evidence that environmental performance and company size directly affect financial performance, environmental performance affects environmental disclosure, while environmental costs and environmental disclosure do not affect financial performance, environmental costs and company size do not affect environmental disclosure. The indirect test results produce evidence that environmental disclosure mediates environmental costs, environmental performance and company size on financial performance. The results, was indicating several implications, including, for companies, they should start to manage the environment well, for example by carrying out environmental performance such as waste and waste management and disclosing environmental performance results as widely as possible in the annual report. This is able to provide important information for stakeholders and the community as additional references in decision making